(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2022)
In the article, the author retraces his experience of participating in the "Nave della legalità", first as a National Anti-Mafia Prosecutor, then as President of the Senate and, finally, as a Senator. By tracing a personal story, he offers an emotional and civic portrait of the journey from Civitavecchia to Palermo, highlighting the enthusiasm and involvement of the students attending.